Efektivitas Pengelolaan Sampah dalam Upaya Pencegahan Kebakaran di TPA Alak Kota Kupang - Fransiska Ena Eki; l Putu Y. B. Pradana; Hendrik Toda; Adriana R. Fallo (Public Service and Governance Journal, 2026)
This study aims to analyze the effectiveness of waste management in preventing fires at the Alak Landfill (TPA) in Kupang City using a qualitative case study approach. Data was collected through interviews, observations, and documentation involving officials from the Environmental and Sanitation Office, landfill workers, waste pickers, and surrounding communities. The findings indicate that the effectiveness of waste management remains low. In terms of input, financial resources, infrastructure, and human resources are insufficient to support optimal operations. During the process stage, waste collection and transportation are hindered by low public compliance, limited vehicles, and minimal waste segregation. Final waste processing still relies on the open dumping method, which increases waste accumulation, methane generation, and fire risks. In terms of output, various mitigation efforts have not successfully reduced the recurring fire incidents due to limited facilities, inadequate compaction, and the absence of gas monitoring systems. The results highlight the need for increased budget allocation, improved facilities, enhanced human resource capacity, and the implementation of safer and more sustainable waste management methods to reduce fire risks at the Alak Landfill.